Implementation of Digital Transformation in the Technical Higher Education Institutions in Tanzania - Raphael, Charles (Tanzania Journal of Engineering and Technology, 2022)
Digital transformation has been prioritized recently in this era of fourth industrial revolution by various organizations for maintaining strong competitive advantage, especially in the fourth industrial revolution. The higher education institutions must likewise adopt and implement digital transformation to enrich their students with the knowledge, experience and the skills they need for a very different future. Technical higher education institutions are inevitable in the given transformation. However, very little is known regarding adoption of digital transformation in the given institutions. This study therefore examined the level of adoption of digital services in the technical higher education institutions in Tanzania. It determined the level of awareness of students on digital transformation, opportunity of students to experience digital technologies in teaching-learning process and determining satisfaction level of students on digital teaching-learning environment. This study applied quantitative approach through the cross-sectional survey design. The data were collected using questionnaire from 500 third year (2019/2020) students of two public technical higher education institutions (i.e., Dar es Salaam Institute of Technology and Arusha Technical College). The collected data were analysed using descriptive statistics and t-test. The results indicate that, students from those two institutions had different levels of awareness on digital transformation. Furthermore, the students from both institutions have low opportunity to experience digital technologies in teaching-learning process. Moreover, the students were partly satisfied on the digital teaching-learning environment in the surveyed institutions. The findings of this study advocate the public technical higher education institutions to fully adopt digital transformation for maximally harnessing the opportunities of fourth industrial revolution through their product students. Keywords: Digital Transformation, Digital Teaching-learning, Digital Environment <table class="MsoNormalTable" style="width: 472.5pt; margin-left: 5.4pt; border-collapse: collapse; mso-yfti-tbllook: 1184; mso-padding-alt: 0cm 5.4pt 0cm 5.4pt;" width="630" border="0" cellspacing="0" cellpadding="0"> Digital transformation has been prioritized recently in this era of fourth industrial revolution by various organizations for maintaining strong competitive advantage, especially in the fourth industrial revolution. The higher education institutions must likewise adopt and implement digital transformation to enrich their students with the knowledge, experience and the skills they need for a very different future. Technical higher education institutions are inevitable in the given transformation. However, very little is known regarding adoption of digital transformation in the given institutions. This study therefore examined the level of adoption of digital services in the technical higher education institutions in Tanzania. It determined the level of awareness of students on digital transformation, opportunity of students to experience digital technologies in teaching-learning process and determining satisfaction level of students on digital teaching-learning environment. This study applied quantitative approach through the cross-sectional survey design. The data were collected using questionnaire from 500 third year (2019/2020) students of two public technical higher education institutions (i.e., Dar es Salaam Institute of Technology and Arusha Technical College). The collected data were analysed using descriptive statistics and t-test. The results indicate that, students from those two institutions had different levels of awareness on digital transformation. Furthermore, the students from both institutions have low opportunity to experience digital technologies in teaching-learning process. Moreover, the students were partly satisfied on the digital teaching-learning environment in the surveyed institutions. The findings of this study advocate the public technical higher education institutions to fully adopt digital transformation for maximally harnessing the opportunities of fourth industrial revolution through their product students.